Assessment of the effectiveness of biological and pharmacological support for training at the preparatory stage for handball players - Vladimir Favoritov; Vadim Gostishchev (Kharkiv State Academy of Physical Culture, 2019)
Based on the analysis of the biological and pharmacological support of athletes, a dietary supplement was chosen to study the effectiveness of the application at the preparatory stage. The presented experimental data indicate that there are positive significant differences between the control and experimental groups of athletes who took dietary supplements of NSP Defense Maintenance. The conducted studies confirm the need for planning the biological and pharmacological support of sports activities in order to increase sports results and prevent and restore athletic health and athletic disabilities. Purpose: to study the effectiveness of the use of dietary supplements with antioxidant effects and with an immunostimulant effect to optimize the functional state of athletes at the preparatory phase. Material & Methods: the studies were organized on the basis of the laboratory of "Biochemistry and Pharmacology of Sports" of Zaporizhzhya National University with the participation of 28 athletes aged 17 to 23 years. In the process of the experiment, the following methods were used: analysis of scientific and methodological literature, generalization of practical experience, pedagogical observations, methods for assessing functional readiness using computer technologies, methods of mathematical statistics. Results: the use of dietary supplements of the NSP Defense Maintenance company positively affected the growth of overall physical performance in athletes in the preparatory period. Conclusion: it is shown that the biological and pharmacological support of training at the preparatory stage is one of the important factors in increasing the efficiency of the training process.